Influence of Organizational Culture, Work-Life Balance, and Digital Literacy on Employee Performance (A Case Study at the General Bureau of the Coordinating Ministry for Political, Legal, and Security Affairs of the Republic of Indonesia) - Dessa, Rima; Hidayat, Rachmat; Mubarok, E. Saefuddin (Jurnal Multidisiplin Sahombu, 2025)
This study explores the influence of organizational culture, work-life balance, and digital literacy on employee performance at the General Bureau of the Coordinating Ministry for Political, Legal, and Security Affairs of the Republic of Indonesia. In the era of rapid digital transformation and increasing complexity of public services, employee performance becomes a critical determinant of organizational success. Organizational culture is examined as a set of shared values and norms that shape behavior and collaboration. Work-life balance is analyzed through employees’ ability to manage responsibilities between work and personal life harmoniously. Digital literacy is viewed as the capacity to effectively use digital tools and critically evaluate digital information in the workplace. The research employs a quantitative approach using survey data to assess the partial and simultaneous effects of the independent variables on performance. The findings are expected to contribute to public sector management by identifying strategic factors that enhance productivity, efficiency, and well-being among civil servants.